Short duration waveforms recorded extracellularly from freely moving rats are representative of axonal activity - Robbins, Ashlee A.; Fox, Steven E.; Holmes, Gregory L.; Scott, Rodney C.; Barry, Jeremy M. (Frontiers in Neural Circuits, 2013)
While extracellular somatic action potentials from freely moving rats have been well characterized, axonal activity has not. We report direct extracellular tetrode recordings of putative axons whose principal feature is a short duration waveform (SDW) with an average peak-trough length less than 179 μs. While SDW recordings using tetrodes have previously been treated as questionable or classified as cells, we hypothesize that they are representative of axonal activity. These waveforms have significantly shorter duration than somatic action potentials, are triphasic and are therefore similar to classic descriptions of microlelectrode recordings in white matter and of in vitro action potential propagation along axons. We describe SDWs recorded from pure white-matter tracts including the alveus and corpus callosum. Recordings of several SDWs in the alveus exhibit grid-like firing patterns suggesting these axons carry spatial information from entorhinal cortical neurons. Finally, we locally injected the GABAA agonist Muscimol into layer CA1 of the hippocampus while simultaneously recording somatic activity and SDWs on the same tetrodes. The persistent activity of SDWs during Muscimol inactivation of somatic action potentials indicates that SDWs are representative of action potential propagation along axons projecting from more distal somata. This characterization is important as it illustrates the dangers of exclusively using spike duration as the sole determinant of unit type, particularly in the case of interneurons whose peak-trough times overlap with SDWs. It may also allow future studies to explore how axonal projections from disparate brain regions integrate spatial information in the hippocampus, and provide a basis for studying the effects of pharmaceutical agents on signal transmission in axons, and ultimately to aid in defining the potential role of axons in cognition.